A spectroscopic approach to assess transport properties of water vapor in PLA. (July 2015) - De Santis, Felice; Gorrasi, Giuliana; Pantani, Roberto
Abstract: The aim of this work is to describe in detail an experimental approach to quantitatively investigate water vapor transport properties in Poly (lactic acid), PLA. The approach is based on in situ time resolved Fourier Transform Infrared Spectroscopy, FTIR, in transmission mode, and provides a mean for monitoring accurately the penetrant sorption kinetics. FTIR spectra were analyzed by a deconvolution procedure, and the area of a specific peak (at 3651 cm -1 ) was directly correlated to the amount of water inside the sample. The time evolution of this area was first normalized by using a peak uninfluenced by the amount of water and then interpolated to obtain the diffusivity parameter. The results were in good agreement with those obtained by more classical, and more complex microgravimetric methods.